Trade Reform and Labor Market Dynamics - Dennis P.J. Botman; Alexander F. Tieman (Tinbergen Institute, 1999)
We present an equilibrium-search model with heterogenous workers whosearch for a job in one of two sectors and who lose part of theirskills during unemployment. We show that an import tariff increasethe wage and the employment prospects in the protected sector. Thisresults in a labor market distortion because it changes thecomparative advantage of the least specialised workers. Trade reformresults in sectoral reallocation of workers which affects employmentin both sectors through quantity and quality effects and increasesunemployment persistently. Replacing the tariff by a wage-costsubsidy financed by means of lump-sum taxation prevents unemploymentfrom rising after trade has been reformed. However, giving a wage-cost subsidy to both sectors is cheapersince then comparative advantage of workers will no longer bedistorted, although unemployment will temporarily rise.
Keywords: F10; J20; J60; D13; D21; 330; Equilibirum-Search model; Comparative Advantage; Trade Reform; Spillovers; Persistence; Subsidies; Außenwirtschaftspolitik; Arbeitsuche; Arbeitsmarkt; Humanressourcen; Arbeitslosigkeit; Theorie